Surface Rupture and Geotechnical Features of The July 2, 2013 Tanah Gayo Earthquake - Daryono, Mudrik Rahmawan; Tohari, Adrin (Indonesian Journal on Geoscience, 2016)
DOI:10.17014/ijog.3.2.95-105An assessment of surface rupture and collateral ground failures can help to evaluate the impact of future earthquakes. This paper presents the results of a field survey conducted to map the surface rupture and geotechnical phenomena associated with the ground shaking during the July 2, 2013 earthquakes in Tanah Gayo Highland. The objectives of this survey are to document and to characterize the surface ruptures as well as to identify types of earthquake-induced ground failures. Results of the survey identified four best sites of possible surface rupture. Two locations are obvious surface ruptures that can be traced on primary topographic feature of the active fault segment from the north to the south, crossing Pantan Terong Hill. The fault segment has a total mapped length of 19 km, with WNW trending zone and a dextral rupture offset. The ground shaking also resulted in landslides and liquefaction in areas underlain by very fine-grained tuffaceous sands. Based on the field survey, it can be concluded that the newly defined active fault segment, the Pantan Terong segment, is likely the segment that ruptured at the July 2, 2013 Tanah Gayo earthquake. Due to the soil types and unstable rocky slopes in the hilly Central Aceh region, large-scale landslides are primary risks during an earthquake event in this region.